2021
DOI: 10.3906/tar-2105-100
|View full text |Cite
|
Sign up to set email alerts
|

Fine root vertical-seasonal distribution of Robinia pseudoacacia in relation to abiotic factors in a chronosequence in coastal saline alkali land of the Yellow River Delta, China

Abstract: Despite the recognized importance of the fine roots in influencing tree growth and stand productivity, knowledge of fine roots is still limited, especially in adverse sites like saline-alkali land. In this paper, we applied sequential soil coring to assess the influence of stand age, soil depth and growth month on fine roots in 3, 16, 30 and 40-year old Robinia pseudoacacia stand in coastal saline-alkali land of the Yellow River Delta, China. Besides, the correlations between fine roots characteristics fine ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also, since root resistance index is known as the most important index against different stresses (49,50), some stadies showed that indices relevant to plant roots can be employed to improve resource capture and plant development under adverse and stressful conditions (51). In addition, other researchers also declared that salinity stress first affects the root system through osmotic stress and reduced water uptake, which then causes ionic toxicity in plants due to nutrient imbalance, Na toxicity, and growth inhibition (11,16,52). As can be seen, our findings (Tables 3 and 4; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since root resistance index is known as the most important index against different stresses (49,50), some stadies showed that indices relevant to plant roots can be employed to improve resource capture and plant development under adverse and stressful conditions (51). In addition, other researchers also declared that salinity stress first affects the root system through osmotic stress and reduced water uptake, which then causes ionic toxicity in plants due to nutrient imbalance, Na toxicity, and growth inhibition (11,16,52). As can be seen, our findings (Tables 3 and 4; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Soil moisture has an important influence on the adaptation of plants in coastal saline lands (Souid et al, 2018). During the rainy season in this region, soil water content increases and soil salinity decreases, but in the dry season the changes are reversed (Souid et al, 2018;Guo et al, 2021). Studies on the halophyte Limonium delicatulum have found that the salt ion content and protective enzyme activity in its aboveground parts were significantly higher in the dry season than in the rainy season (Souid et al, 2018), and osmoregulatory substances had similar changes (Maaloul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…and how the currently existing woody plants will react to environmental changes? have been raised [2][3][4]. The majority of literature is predicated on the link between climate and treeline.…”
Section: Introductionmentioning
confidence: 99%